Horizontal axis hydrometric current meter with reference to the french experience. What future for this technique?. Issue 5 (1st October 2018) - Perret, C.; Lallement, C.; Belleville, A.
Abstract : According to the results of a survey conducted in 2017 amongst hydrometric network operators in France, Luxembourg, Switzerland and Wallonia, 25% of their gauging activity is carried out using horizontal-axis current meters. As this measurement technique is still in use, the authors considered it useful to assemble a bibliographic overview which summarizes (i) the evolution of the horizontal-axis current meter (ii) the alternative North American choice of vertical-axis technology (iii) the principles for calibrating these devices and their evolution (iv) a review of case studies on influential factors (v) developments in the techniques for implementing these current meters. In conclusion, some of the reasons for retaining this type of equipment in the expertise toolbox of hydrometric network operators are briefly presented in this article. The authors have, as far as possible, sought to portray the French practice in relation to those of other countries. This is used to illustrate the wide array of inputs from each player and the development of the French practice compared to that of the international world of hydrometry.